The Effect of Child Care Costs on Gender Inequality - Alessandra Casarico; Elena Del Rey; José Ignacio Silva (Center for Economic Studies and ifo Institute (CESifo), 2022)
We develop a model to study the impact on gender gaps in participation and wages of a liquidity constraint that prevents some households from paying child care. We show that this liquidity constraint generates an inefficiency and amplifies gender gaps in the labour market. In this framework, an extension of paid maternity leave duration has ambiguous effects on gender inequality. In contrast, child care subsidies, which require higher taxes, and loans, which do not, unambiguously reduce gender inequality. We illustrate the mechanisms at play in a numerical example using Spanish data.
Keywords: J16; J18; J13; 330; liquidity constraints; gender wage and participation gaps; statistical discrimination; numerical example